The Performance of Library Observers at the Sinjai Regency Library and Archives Service in Encouraging and Increasing Young Generation's Reading Interest - Juniati, Sri Rahayu; Adiputra, Muhlis Hajar; Nurhikmah, Nurhikmah (Universitas Negeri Makassar, 2022)
The library as it exists and is developing, has now been used as a center for information, a source of knowledge, research, recreation, preservation of the nation's cultural treasures, as well as acting in other services. The purpose of this study was to determine how the performance of library observers at the Sinjai Regency Library and Archives Service in encouraging and increasing interest in reading for the younger generation. This study uses a qualitative descriptive type of research to provide a clear description and overall description of the performance of the Library Observer in encouraging and increasing the reading interest of the younger generation. Data collection techniques used are observation, interviews and documentation. The informants in this study were the Head of the Office of the Library and Archives of Sinjai Regency, Library Observer Management, and Library Visitors. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of data analysis show that the performance of Library Observers at the Library and Archives Service of Sinjai Regency in encouraging and increasing reading interest of the younger generation is less effective, because its contribution is less than optimal in carrying out its duties and functions.